Implementing and Managing the Teaching Factory Learning Model at Vocational Schools - Alexius Dwi Widiatna; Purwani Puji Utami; Isthifa Kemal (Jurnal Penelitian Pendidikan IPA, 2025)
This research explores the implementation and management of the teaching factory (TEFA) models at Vocational High School (SMK) St. Mikael, Surakarta, Indonesia. The research focuses on the management of production units owned by the school and how the school collaborated in industrial cooperation with relevant enterprises. A qualitative approach with a case study method was employed, collecting data through documentation, interviews, and observation. The findings reveal that the teaching factory is implemented through block schedules and job sheets to enhance student skills, with professional management of the production unit. Additionally, the industrial cooperation bridged by the school and its business partners has involved apprenticeships, product marketing, worker deployment, and industrial work visits. Among these four programs, apprenticeships are believed to be the most effective in enhancing students' vocational competencies. Implementing the TEFA model has assisted the school in equipping its students with competencies aligned with the industrial demands for qualified and competent workers. The study suggests that other vocational schools implementing TEFA might consider managing their production unit by employing block schedules and job sheets in the production unit, and building industrial partnerships to address the demand of the current industry trends.